2001
DOI: 10.1152/ajplung.2001.280.2.l258
|View full text |Cite
|
Sign up to set email alerts
|

The NO donor molsidomine reduces endothelin-1 gene expression in chronic hypoxic rat lungs

Abstract: We investigated the effects of the nitric oxide (NO) donor molsidomine and the nitric oxide synthase inhibitor N-nitro-L-arginine methyl ester (L-NAME) on pulmonary endothelin (ET)-1 gene expression and ET-1 plasma levels in chronic hypoxic rats. Two and four weeks of hypoxia (10% O2) significantly increased right ventricular systolic pressure, the medial cross-sectional vascular wall area of the pulmonary arteries, and pulmonary ET-1 mRNA expression (2-fold and 3.2-fold, respectively). ET-1 plasma levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…This increased ET-1 release was associated with an increase in ET-1 transcription (36). Conversely, treatment with the NO donor molsidomine reduced the hypoxia-induced increase in ET-1 release in the lungs of rats (7). Although the exact mechanism of the interaction was not resolved, these data indicate that NO and ET-1 have an inverse relationship and provide important information in the context of the regulation of the two vascular mediators.…”
Section: Discussionmentioning
confidence: 84%
“…This increased ET-1 release was associated with an increase in ET-1 transcription (36). Conversely, treatment with the NO donor molsidomine reduced the hypoxia-induced increase in ET-1 release in the lungs of rats (7). Although the exact mechanism of the interaction was not resolved, these data indicate that NO and ET-1 have an inverse relationship and provide important information in the context of the regulation of the two vascular mediators.…”
Section: Discussionmentioning
confidence: 84%
“…After 4 weeks, right ventricular systolic pressure was determined in all animals with the closed‐chest technique as previously described (Blumberg et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Indeed (Nakanishi et al 1999), found in a model of hypobaric hypoxia-induced PH increased ET-1 mRNA and protein by in situ hybridization and immunohistochemistry in smooth muscle cells, yet unchanged in endothelial cells of pulmonary arteries, implicating an autocrine role for ET-1 in the remodeling process. Other studies report elevations or reductions of modulating factors in hypoxic vasoconstriction and vascular remodeling, for example the ET B receptor, NO synthase protein and NO (Blumberg et al 2001;Ivy et al 2001;Muramatsu et al 1999), as well as invoking a role for ET-3 (Pfeifer et al 1998).…”
Section: Ph Associated With Disorders Of the Respiratory System And (mentioning
confidence: 99%